Pengembangan Media Pembelajaran Berbasis MindManager Konsep Struktur dan Fungsi Organ Tumbuhan pada Siswa Sekolah Menengah Pertama - Nurlia Ali; Sulasmi Anggo (Magister Pendidikan Biologi, Universitas Negeri Medan, 2018)
Abstract: This study is a research and development, which aims to produce instructional media, based MindManager that valid, practical and effective. The subjects were eighth grade students of SMP 27 Makassar by the number of students 39 people. This study uses the research and development according to Borg and Gall. Data collection techniques used in this research is the data on validation results obtained from the validation instrument sheet filled out by the valuator, the data for practicality level obtained from questionnaires that filled out by the valuator and practitioners, the data for effectiveness obtained from questionnaire of students' responses and mastery of student learning outcomes by intructional media based on MindManager. The data obtained from the study were analyzed using the criteria of validity, practicality and effectiveness by Hobri. The research results of development instructional media based on MindManager shows that the total value of the validation results by valuator are 4.42 and included in the valid category. The average level of practicality by valuator questionnaire was 91.33% and 90.66% by practitioners. The effectiveness of the media based on the student response was 96.6% gave a positive response and mastery of learning outcomes is 89.7% of the subjects achieved a minimum level of mastery of the material. Based on these results it can be concluded that the instructional media based MindManager developed by validity, practicality and effectiveness criteria.